TREN PENELITIAN TEKNOLOGI PEMBELAJARAN JARAK JAUH : - Winoto, Yunus; Septian, Falih Ijal; Nurarni, Sri Ageng (Universitas Galuh, 2025)
Distance learning technology is a topic that is widely discussed. The distance learning phenomenon is a trend in technological development that makes learning easier for students and lecturers. In this way, the author created this research and aims to present and map the results of bibliometric analysis regarding the topic of distance learning technology to find out how many people are discussing this topic. The data set for this research was taken from the Scopus database with a publication time span of 2013-2023 with results of 534 articles available. This research uses the R-bibliometric package biblioshiny webinterface to analyze and visualize data obtained from the Scopus database. The results of the research show that the topic of distance learning technology has been widely researched by authors from several countries with evidence from the tables of most relevant authors, citations by country, authors by country, author collaborations, publications by country, journal publications, most affiliations, and local authors based on H -index. Then the trending keywords for this topic are education, human, articles, students, and e-learning. This can be seen from the presentation of the wordcloud map and thematic map.